Judo exercises increase emotional expression, self-control, and psychological resilience - Köroǧlu, Mihraç; Yılmaz, Coşkun; Tan, Çetin; Çelikel, Baha Engin; Budak, Cemalettin; Kavuran, Korhan; Susuz, Yunus Emre; Barut, Yaşar; Ceylan, Tülay; Soyer, Fikret; Sezer, Süreyya Yonca; Şahin, Fatma Neşe (Frontiers in Psychology, 2025)
BackgroundThe extant research on judo sports has principally concentrated on the physiological effects of training. Conversely, there has been limited attention paid to studies on psychological resilience, self-control, and emotional expression levels. The present study examined the effects of Judo exercises on psychological resilience, self-control, and emotional expression levels in healthy male subjects.MethodsThe present study comprised 50 healthy, sedentary male subjects. The subjects were randomly divided into two groups: one group participated in judo training (JT) and the other group served as the control group (CON). The sample sizes for the JT and CON groups were both 25. The JT group underwent judo training, while the CON group maintained their usual lifestyle. The Brief Psychological Resilience Scale, the Multidimensional Brief Self-Control Scale, and the Berkeley Emotion Expression Scale were administered prior to and following the 6-week training period.ResultsThe study demonstrated that a 6-week judo training regimen exerted a significant effect on the psychological resilience score (e.s. = 1.047, p < 0.001), while no such effect was observed in the Control group (e.s. = 0.0091, p = 0.751). In the context of self-control levels, an effect was observed on the Initiation sub-dimension (e.s. = 1, 739, p < 0.001), yet no effect was found on the Inhibition dimension (e.s. = 0.052, p = 0.892). In the control group, a significant decrease was identified in the Initiation sub-dimension (e.s. = 0, 785, p = 0.001) and Inhibition sub-dimension (e.s. = 1, 861, p < 0.001). The findings indicate that impulse power (e.s. = 0.395) and concealment (e.s. = 0.428) exerted a negligible influence on the emotional expression sub-dimensions. Conversely, psychological resilience (e.s. = 0.886) demonstrated a substantial impact.ConclusionsThe judo exercises demonstrated a favorable impact on psychological resilience, self-control, and emotional expression levels in healthy male subjects. The findings of this study may offer significant insights into the impact of judo exercises on psychological resilience, self-control, and emotion expression levels. These findings could serve as a guide for the development of future interventions and program design in the domain of sport psychology.